THE EFFECT OF ETHANOLIC EXTRACT OF DAYAK ONION (Eleutherine palmifolia (L) MERR) TUBER ON BLOOD GLUCOSE AND INSULIN LEVEL OF STREPTOZOTOCIN-INDUCED DIABETIC WISTAR RAT - Yaturramadhan, Hasni; Dalimunthe, Aminah; Widyawati, Tri (Asian Journal of Pharmaceutical Research and Development, 2019)
Objectives: The current investigation was conducted to examine the ability of ethanolic extract from onion dayak (Eleutherine palmifolia) (L) (Merr) tuber to reduce blood glucose and increase insulin production in streptozotocin-induced diabetic wistar rat. Materials and Methods: Extraction was accomplished using maceration method with 96% ethanol. Antidiabetic activity was evaluated using observation of blood glucose levels utilize glucometer (Easy Touch). Analysis of insulin plasma concentration was determined utilize the Insulin Elisa Kit (Chem Cruz). Results: The administration of dayak onion extract as a form of therapy in diabetes, although it has not been able to increase insulin levels significantly, but has shown a tendency to increase insulin levels at higher doses of 500 mg/bw. Conclusion: Ethanolic extract from dayak onion tuber exhibited activity of decrease blood glucose level and increase plasma insulin concentration in streptozotocin-induced diabetic wistar rat.